MEETING THE NEW CHANGES THROUGH THE TRAINING OF YOUNG PROFESSIONAL - Hasa, Daniela (PROFESSIONAL STUDIES: Theory And Practice, 2022)
Young professionals are facing greater challenges during the transition from the academic world to the professional one. This paper provides an overview of the current situation of pre-service teachers’ professional internship, and it elaborates the main needs, shortcomings, and possible proposals. It inquires into the role of educational institutions in this process and recommends a potential model and an effective CPD program to support preservice teachers in meeting the new changes and challenges